Low to Moderate Dose Anthracycline-Based Chemotherapy is Associated with Early Noninvasive Imaging Evidence of Subclinical Cardiovascular Disease - Drafts, Brandon C. (2013)
OBJECTIVE: To determine if low to moderate doses of anthracycline-based chemotherapy (Anth-bC) are associated with subclinical cardiovascular (CV) injury. BACKGROUND: Cancer survivors that receive Anth-bC experience premature CV events. It is unknown whether low to moderate doses of anthracyclines a) promote early subclinical CV disease manifested by deteriorations in left ventricular ejection fraction (LVEF) or increases in aortic stiffness, or b) are associated with change in quality of life (QOL). METHODS: In 53 men and women with breast cancer, leukemia, or lymphoma, we assessed left ventricular volumes, LVEF, circumferential strain, aortic pulse wave velocity (PWV), late gadolinium enhancement, serum B-type natriuretic peptide (BNP), troponin I (TnI), and the impact of treatment on QOL before, and 1, 3, and 6 months after receipt of Anth-bC. RESULTS: Participants averaged 50±2 (range 19–80) years in age, 58% were women, 17% were black, and they each received a range of 50 to 375 mg/m(2) of doxorubicin equivalent chemotherapy. Left ventricular end systolic volume (LVESV; 48±3 to 54±3 ml; p=0.02), left ventricular strain (−17.7±0.4 to −15.1±0.4; p=0.0003), PWV (6.7±0.5 to 10.1±1 m/sec; p=0.0006), and QOL deterioration (15.4±3.3 to 28.5±3.9; p=0.008) increased, while LVEF (58±1 to 53±1%; p=0.0002) decreased within 6 months after low to moderate doses of Anth-bC. All findings persisted after accounting for age, gender, race (white/black), doxorubicin equivalent dose, doxorubicin administration technique, comorbidities associated with CV events, and cancer diagnosis (p=0.02 to 0.0001 for all). There were no new late gadolinium enhancement findings after 6 months. CONCLUSIONS: Low to moderate doses of Anth-bC are associated with the early development of subclinical abnormalities of cardiac and vascular function that in other populations are associated with the future occurrence of CV events.